(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
The proposed work is to apply a wavelet based image fusion algorithm is applied on the Magnetic Resonance (MR) images and Computed Tomography (CT) images which are used as primary sources to extract the redundant and complementary information in order to enhance the tumor detection in the resultant fused image. The main features taken into account for detection of brain tumor are location of tumor and size of the tumor, which is further optimized through fusion of images using various wavelets, transforms parameters. The performance efficiency of the algorithm is evaluated on the basis of PSNR values.